Extraction, Characterization and Application of Natural Dye Extract from Beetroot (Beta vulgaris) on Cotton Fabric - Johnson, Gani; Yakubu, Joshua; Atoshi, Ago Mikyitsabu; Emmanuel, Sarki Atoma-ti (Darul Yasin Al Sys, 2024)
Using a Soxhlet system, natural dye was extracted from beetroot (Beta vulgaris) and applied to cotton fabric. With the use of FT-IR, GC-MS, and UV-visible spectroscopy, the extracted dye was analyzed. On the cotton cloth that had been dyed, the properties of scouring, wash fastness, and light fastness were assessed. Using a mordant, the cotton fabric was treated with the natural dye extract. The dye extract has a red colour. According to the FTIR characterization data suggested the presence of N-H, C-H, C=C, C-H, C-N and C-Cl functional groups in the dye extract. Fifty one compounds were isolated and identified by the GC-MS Melezitose, 5-Hydroxymethylfurfural and 4-Mercaptophenol has the higest percentage area (70.19 %) and Cis-10-Nonadecenoic acid, 9-Octadecenoic acid, (E)-, and cis-Vaccenic acid has the lowest percentage area (0.07%). N-H and C=C were the chromophores found in the dye extract.The color fastness to wasshing test revealed that the materials' fastness grade increased to a range of 3, indicating a fair grade of fastness, when the dye was applied using SnCl2 as a mordant.While the color fastness to light showed that cotton fabric was dyed with mordants, the fastness grade increased to a range of 5, which indicates a moderate fading resistance, when the dye was applied to the fabrics using FeSO4 as the mordant. Using K2Cr2O7 as the mordant, the fastness grade slightly decreases to a range of 1, indicating very poor grade of fastness. The result of colour fastness and SnCl2 light fastness of the dye demonstrated a moderate resistance to fading and a fair color look on cotton fabric. The colour fastness to rubbing showed that 3-4 and 2-3 colour changes were experienced for dry and wet rubbing respectively with mordant. The outcome of colour fastness of the dye showed a very good affinity to remain on the fabric when mordant was applied.